2013
DOI: 10.2166/9781780401249
|View full text |Cite
|
Sign up to set email alerts
|

Animal Waste, Water Quality and Human Health

Abstract: The excreta (faeces and urine) of mammals and birds are widespread across planet Earth and frequently contaminate water that is used for bathing and recreation, that is treated and distributed for human consumption, and that is used to irrigate crops.The risk that such contamination represents to human health is inadequately understood. It is widely assumed that faeces of animals represents a lesser risk to human health than human faeces of because of the 'species barrier' and especially the species-specificit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 516 publications
(695 reference statements)
0
39
0
Order By: Relevance
“…Evidence of soap served as an indicator for hand washing, thus lack of soap suggests reduced hand washing by the household. Handwashing with soap is especially critical in preventing food and water contamination [7] by ruminants [60], can reduce diarrheal disease risk by between 40% and 65% [61,62], and can protect against exposure to enteric zoonoses found in animal waste [63]. Although good hand hygiene is particularly protective at certain critical times [59], self-reported handwashing rates in this study population were only 20% before food preparation, 27% before eating, 20% before feeding children, 42% after cleaning children, and 76% after using the toilet.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of soap served as an indicator for hand washing, thus lack of soap suggests reduced hand washing by the household. Handwashing with soap is especially critical in preventing food and water contamination [7] by ruminants [60], can reduce diarrheal disease risk by between 40% and 65% [61,62], and can protect against exposure to enteric zoonoses found in animal waste [63]. Although good hand hygiene is particularly protective at certain critical times [59], self-reported handwashing rates in this study population were only 20% before food preparation, 27% before eating, 20% before feeding children, 42% after cleaning children, and 76% after using the toilet.…”
Section: Discussionmentioning
confidence: 99%
“…However, this practice can lead to a public health risk. Unsafe handling and disposal of animal waste put residents at risk for zoonotic disease, regardless of household ownership as domestic animals can generate waste that pollutes shared community space (World Health Organization, ). Animal waste can contaminate public locations or local water sources used for recreation or drinking by rainfall, soil movement and waste disposal and management practices of farmers.…”
Section: Discussionmentioning
confidence: 99%
“…The use of water for different purposes such as drinking, household, industrial, agricultural (irrigation), swimming and other recreational purposes makes it possible for the spread of diseases such as typhoid and dysentery in human population [4]. It has been reported that waterborne zoonosis can be a serious problem especially in the developing countries that lacks adequate water treatment facilities and hence make use of untreated wastewater [5]. Typhoid fever caused by the bacterium Salmonella accounts for several cases of morbidities and mortalities in Nigeria [6].…”
Section: Introductionmentioning
confidence: 99%